Utilizing digital tools to support face-to-face care: Examining uptake within the practices of Australian psychologist - Kerr, Jeremy; Houten, Ashley Van (Human Technology, 2020)
Societal adoption of mobile phones and other digital devices, and the resulting widespread digital literacy, allows for new possibilities in approaching and supporting face-to-face therapy. In this study, we examined the application of digital communication tools and media within therapeutic care by 33 psychologists across Australia. Uses of digital technologies were analyzed with a focus on both the approaches applied within face-to-face therapy sessions and those occurring as an adjunct to these sessions. In contrast to online counseling, established upon a foundation of digital technologies, the study results indicate that the use of technology in face-to-face therapy is still emerging but growing in scope and implementation. Areas of key and unique uptake by practitioners are identified, along with possibilities for future application. In outlining contemporary practices, a typology for the utilization of digital tools is presented, offering a practical framework for therapists to extend face-to-face care via information and communication technologies.